Smoking and HIV: what are the risks and what harm reduction strategies do we have at our disposal? - Michelle L. Giles; Coral Gartner; Mark A. Boyd (AIDS Research and Therapy, 2018)
Abstract The World Health Organization estimates that smoking poses one of the greatest global health risks in the general population. Rates of current smoking among people living with HIV (PLHIV) are 2–3 times that of the general population, which contributes to the higher incidence of non-AIDS-related morbidity and mortality in PLHIV. Given the benefit of smoking cessation, strategies to assist individuals who smoke to quit should be a primary focus in modern HIV care. Tobacco harm reduction focuses on reducing health risk without necessarily requiring abstinence. However, there remains uncertainty about the safety, policy and familiarity of specific approaches, particularly the use of vaporised nicotine products. Evidence suggests that vaporised nicotine products may help smokers stop smoking and are not associated with any serious side-effects. However, there is the need for further safety and efficacy data surrounding interventions to assist quitting in the general population, as well as in PLHIV specifically. In addition, official support for vaping as a harm reduction strategy varies by jurisdiction and this determines whether medical practitioners can prescribe vaporised products and whether patients can access vaporised nicotine products. When caring for PLHIV who smoke, healthcare workers should follow general guidelines to assist with smoking cessation. These include: asking the patient about their smoking status; assessing the patient’s readiness to quit and their nicotine dependence; advising the patient to stop smoking; assisting the patient in their attempt to stop smoking through referral, counselling, pharmacotherapy, self-help resources and/or health education; and arranging follow-up with the patient to evaluate their progress.